Implementation of Digital Marketing to Increase Satisfaction and Impact on the Image of Banking PT. Bank Central Asia Tbk - Mohamad Arfiman yosep; Yoyo Sudaryo; Astrin Kusumawardan; Nandan Limakrisna (DINASTI RESEARCH, 2020)
The banking industry currently wants to provide the best service to the public because of the many bank expansion that has just sprung up but already offers a lot of banking convenience services. This begins with the application of digital marketing that makes it easy for customers to make transactions. Digital marketing is very easy because transactions can be done only through smartphones or other devices. Some banks have services such as internet banking, mobile banking, SMS banking, and customers can now create new accounts using only their smartphones. This makes digital marketing a new service prima donna in providing services to the public in the banking world in Indonesia. The research method used in this research is descriptive and verification research. A descriptive method is a method in examining the status of a group of people, the status of an object, a set of conditions, a system of thought, or a class of events in the present